The Influence Of Compensation And Motivation On Employee Performance At The Tamansari Semanggi Apartment - Naomi Caroline; Pipin Sukandi (International Journal of Social Service and Research, 2023)
Human resource management organizes, coordinates, and manages the acquisition, reconciliation improvement, support and end of employment relationships entirely aimed at achieving organizational goals in a coordinated manner. Through careful HR planning, a representative's level of presentation can be substantially expanded. The aim of this research is to examine how compensation and motivation impact the performance of employees in the Tamansari Semanggi Apartment. This scholarly article employs quantitative data collected through the distribution of questionnaires. The research utilizes purposive sampling, involving a sample of 130 employees from the Tamansari Semanggi Apartments. The analysis of the data includes instrument tests such as tests for validity and reliability, multiple regression analysis, and traditional assumption tests such as multicollinearity, heteroscedasticity, and normality testing. Furthermore, hypothesis testing involves t-tests, f-tests, and coefficient of determination tests. The research results show that compensation variables partially do not affect employee performance, motivation variables partially affect employee performance, and compensation variables and motivation variables simultaneously affect employee performance